Analysis of Deflection and Moment Capacity on the Precast Beam of the Nk-Spircon Connecting System - Huda, Miftahul; Mursidi, Hary; Wiwoho Mudjanarko, Sri; Mulyo Utomo, Wahyu (International Journal of Engineering and Technology, 2018)
This study is a case study on the planning of a multilevel building of the Faculty of Medicine, University of Wijaya Kusuma Surabaya, which aims to compare the strength of precast beam structure using NK-SpirCON connection system with conventional beam (cast in situ). The model of building structure and beam used is the result of consultant planning modified into precast beam with dimension and number of reinforcement according to planning result where connection between beam and column is used NK-SpirCON connection system. The test is done in collaboration with the number of specimens according to the number of variations of the existing beam type. The test is performed by gradually loading the load on the specimen to calculate the maximum load, maximum deflection and acceptable capacity moments of the beam. The results conclude that the precast beam using NK-SpirCON connection system has the ability to receive larger deflection and moment capacity than the conventional beam (cast in situ) with 29,81 % and 34,64 % difference. For further research it is advisable to research the shear strength of the beam and the strength of the connection between the beams and the columns due to various loads including quasi dynamic loads according to the prevailing regulations and regulations in Indonesia.Â Â